Two-dimensional spatial distribution modeling of sprinkler irrigation - Ferreira Borges Júnior, João Carlos; de Lelis Teixeira de Andrade, Camilo (Revista Ceres, 2025)
Irrigation can provide significant agronomic and financial returns on agricultural activity. The maximization of the benefits obtained from irrigation depends, among other factors, on the water use efficiency, which is intrinsically related to application uniformity. For the sprinkler method, the irrigation uniformity assessment is based on results of labor-intensive field tests in which the two-dimensional water distribution pattern is measured in a grid of catch cans. The aim of this study was to evaluate a simplified methodology for determining the irrigation uniformity using water depth distribution data of a single sprinkler head in operation, positioned at the intersection of two diagonal alignments containing regularly spaced catch cans. Three methods to simulate the spatial water distribution on the alignments were evaluated: linear interpolation (LI), cubic spline (SC) and second-degree polynomial regression (PR). Each of these methods were associated with a procedure to calculate the two-dimensional spatial water distribution. The adequacy of the LI and SC modeling methods was verified by using the Wilcoxon-Mann-Whitney test (p-value < 0.05) applied to the data of the field tests. Mean values of the coefficient of efficiency equals to 0.771 and 0.785 were obtained for the LI and SC methods, respectively. The PR method underperformed the others.